The Effect of Oxytocin Massage on Weight among Infant in Sub-Urban and Rural Areas - Purnamasari, Kurniati Devi; Hindiarti, Yudita Ingga (Alta Dharma Publisher, 2023)
Background: The World Health Organization (WHO) recommends exclusively breastfeeding for six months. In addition to the advantages of breastfeeding, one of the critical challenges is the issue of exclusive breastfeeding, namely the uneven milk production. In the medical setting, pharmacological therapy is used post-partum to encourage breastfeeding. Unfortunately, this approach makes the mother dependent on the child. A non-invasive method of increasing milk supply, oxytocin massage is safe for mothers. Objective: This study aims to ascertain how oxytocin massage affects infant weight gain. Method: This study has a quasi-experimental design and is an experiment. There were 46 participants in this study. Purposive sampling was used to collect samples from 30 post-partum women randomly split into two groups, 15 of whom received oxytocin massages and 15 of whom received breast care. Result: According to the statistical test results, the intervention group's oxytocin massage had a substantial impact on the infants' weight being reached. The findings of this study will raise the standard of care provided by healthcare professionals, particularly midwives acting in the capacity of executors, who will be better able to inform mothers about the advantages of oxytocin massage and inspire families to engage in it. Conclusion: Due to the study's findings, providing the intervention group with an oxytocin massage significantly increased milk production as measured by the quantity of milk produced, the baby's weight, the frequency of feedings, and the frequency of urine. During the post-partum phase, the mother receives an oxytocin massage. Recommendation: The findings of this study would enhance the standard of care provided by healthcare professionals, particularly midwives who serve as executors. It may inform mothers about the advantages of oxytocin massage and inspire families to undertake it.